Plant gnotobiology: Epiphytic microbes and sustainable agriculture - Kutschera, Ulrich (Plant Signal Behav, 2016)
In 1963, a monograph by Thomas D. Luckey entitled Germfree Life and Gnotobiology was published, with a focus on animals treated with microbes and reference to the work of Louis Pasteur (1822–1895). Here, we review the history and current status of plant gnotobiology, which can be traced back to the experiments of Jean-Baptiste Boussingault (1801–1887) published in 1838. Since the outer surfaces of typical land plants are much larger than their internal areas, embryophytes “wear their guts on the outside.” We describe the principles of gnotobiological analyses, with reference to epiphytic metylobacteria, and sunflower (Helianthus annuus) as well as Arabidopsis as model dicots. Finally, a Californian field experiment aiming to improve crop yield in strawberries (Fragaria ananassa) is described to document the practical value of this novel research agenda.